مشكلات معلمي الطور الابتدائي وسبل حلها - مسعودي, مروة; بالطاهر, النوي (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى هدفت هذه الدراسة للكشف على مشكلات معلمي الطور الابتدائي وطرح حلول لها، إذ تكونت عينة الدراسة من (36) معلما ومعلمة، وتم تطبيق أداة الدراسة التي أعدها الباحث الطيار سلطان بن علي بن عبد الرحمان (2008) الذي تم بناءه في المملكة العربية السعودية، وتم التحقق من صدقه وثباته بالدراسة الاستطلاعية، وقد جرت المعالجة الإحصائية للنتائج باستخدام البرنامج الإحصائي للإجابة على تساؤلات الدراسة. وقد بينت النتائج أن المشكلات المتعلقة بالتدريب على المناهج المطورة هي قلة الوقت المخصص لتدريب المعلمين على المناهج المطورة وضعف ارتباط أهداف البرامج التدريبية بالمشكلات التعليمية والسلوكية للطلاب. في حين مشكلات المتعلقة بتطبيق المناهج المطورة هي ضعف المعلمين في تفعيل الأنشطة التعليمية المصاحبة للكتاب المدرسي وضعف مهارات المعلمين المتعلقة بتطبيق استراتيجيات التدريس المناسبة للمناهج المطور. أما مشكلات معلمي الطور الابتدائي المتعلقة بمهارات التقويم المستمر فهي ضعف كفاية المعلم بمهارات التقويم المستمر أثناء الخدمة وضعف استفادة بعض المعلمين من التغذية الراجعة للتقويم المستمر. كما تم تقديم بعض المقترحات التي من شأنها أن تساهم في التخلص من المشكلات المتعلقة بمعلمي الطور الابتدائي. Abstract: This study aims at this study aimed at exploring the problems of primary school teachers and proposing solutions for them, as the study sample consisted of (36) teachers, and the study tool prepared by the pilot researcher Sultan bin Ali bin Abdul Rahman (2008) that was built in the Kingdom was applied The results were verified by using the statistical program (spss) to answer the study’s questions.The results showed that the problems related to training on the developed curricula are the lack of time allocated to training teachers on the developed curricula and the weak linkage of training programs ’objectives with students’ educational and behavioral problems. While the problems related to the application of the developed curricula are the teachers ’weakness in activating the educational activities accompanying the textbook and the weakness of teachers’ skills related to the application of teaching strategies appropriate to the developed curriculum. As for the primary phase teachers ’problems related to continuous evaluation skills, they are the weakness of the teacher's adequacy of continuous evaluation skills during service and the weak benefit of some teachers from the feedback for continuous evaluation. Some proposals were also made that would contribute to eliminating problems related to primary school teachers.
دراسة ميدانية على معلمي ابتدائية غرايسة العروسي وابتدائية كراسع عبد الرزاق بالحمادين
مقال
Keywords: مشكلات معلمي الطور الابتدائي ; الطور الابتدائي; Primary teachers' problems; Elementary phase